LOW-TECH INNOVATION AND LOCAL ECONOMIC DEVELOPMENT: CASE STUDY THE TRADITIONAL BATIK INDUSTRY IN PEKALONGAN MUNICIPALITY - Nimas Maninggar; Delik Hudalah (Diponegoro University, 2018)
Innovation is no longer purely a project of high-tech industries. The decade has seen a paradigm shift of the meaning and the process of innovation creation from a linear model that largely focuses on R&D, toward a non-linear model through informal and interactive processes. As a result, low-tech industries with a low level of R&D can also make innovations and benefit the regional economy. In Indonesia, such innovation may be linked to the development and survival of cultural industrial clusters. One of Indonesia’s unique cultural industries is batik. Using a qualitative analysis, this paper explores the impact of process and product innovations in the batik industry on the local economic development of Pekalongan Municipality, Indonesia’s largest batik-producing city. The study is based on semi-structured interviews with batik entrepreneurs, which show that innovations have contributed to the cutting of production costs and, thus, increasing the industrial units’ income; the emergence of new batik entrepreneurs; and an increase in tourist visits, supporting businesses and facilities.